The existence and multiplicity of nontrivial solutions for a class of p-Monge-Ampère system - Ya-nan, Ma; Chenghua, Gao; Huanhuan, Ding (Topological Methods in Nonlinear Analysis, 2026)
In this paper, we deal with the following p-Monge-Ampère system: equation* cases det(D(|Du_1|^p-2Du_1))=f_1(|x|,-u_2), & xB, det(D(|Du_2|^p-2Du_2))=f_2(|x|,-u_1),& xB, u_1=u_2=0, & xB, cases equation* where B={xR^n:|x|< 1} and f_i (i=1,2) are continuous and nonnegative functions. Based on the fixed-point theory, some results regarding existence of radial solutions are established when f_i (i=1,2) satisfy some new growth conditions.